AXIOLOGICAL GROUNDS OF ARGUMENTATION IN THE INTERNET DISCOURSE OF HEALTH PSYCHOLOGY - S. V. Shevyakina (Гуманитарные и юридические исследования)
This article is devoted to the analysis of argumentation in the perspective of its axiological grounds. As part of the review, different interpretations of argumentation as a polyaspectual notion are considered. Traditionally, logical, rhetorical and cognitive models of argumentation are distinguished. A systematic model presents argumentation as an integral system in which logical, cognitive, rhetorical and axiological constituents coexist. Specificity of argumentation and methods of its structuring are connected with the discursive situation and determined by the parameters of the discourse. We define the discourse of health psychology as hybrid as it combines characteristics of institutional and personal discourses. The analysis of argumentation in the discourse of health psychology indicates that the axiological constituent of argumentation is represented at the level of determinants (axiological dissonance), at the level of the participants of argumentative action (axiological image of the author, axiological image of the recipient) and in the schemes (models) of argumentation. Argumentative impact which takes the forms of persuasion and motivation provides conditions to maneuver the actors of argumentative process. Application of a logic and axiological model based on the language of judgement logic and inference reconstruction made it possible to conclude that both the assumptions and the conclusion contain values as abstract notions. This fact demonstrates that argumentation is based on values. In the rhetorical perspective of argumentation values are integrated into the structure of a value judgement and are represented in the epideictic type of argumentation by means of the argument “model and antimodel” and the argument of ascension. The study outcomes specify positions of values as basic elements in the argumentation structure and offer prospects to research argumentation in different types of discourse.